Živnostenský zákon - Svoboda, Radek (Univerzita Pardubice, 2006)
Bakalářská práce na téma " Živnostenský zákon"je rozdělena do dvou částí. První část vymezuje základní pojmy živnostenského zákona. Druhá část popisuje Obecní živnostenský úřad Havlíčkův Brod, vývoj živnostenských oprávnění v tomto okrese a základní otázky dalšího vývoje.

This bachelor work on the theme " The trades licensing act" divided into two parts. The first part of the bachelor work defines the basic terms of the Trades Licensing Act. The second part describes the Municipal Trades Licensing Office of Havlíčkův Brod, and the basic aspects of a future development.
The trades licensing act
Keywords: Trades licensing act; trades licensing office; trade licence; business environment; Živnostenský zákon; živnostenský úřad; živnostenské oprávnění; podnikatelské prostředí